Village Political Education in Increasing the Political Literacy of the People of Deli Serdang Regency - Bahri, Saipul; Kusmanto, Heri; Subhilhar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Political education is a form of effort to increase quality political participation which can be seen from the public's understanding of the importance of elections and democracy to society and is also a forum for the actualization of the Tri Dharma of Higher Education, amidst pragmatic political uncertainty which only involves the public at times of political momentum, which often increases. Money politics is caused by a lack of public literacy regarding political conditions and information. Political education is part of the effort to increase the knowledge of the Tuntungan II Village community which includes the Village Youth Organization, business actors and the community amidst increasingly advanced democratic flows. In this service plan, the team will implement service in Tuntungan II Village, Pancur Batu District, Deli Serdang Regency The sub-district is the locus, because Tuntungan II Village is one of the villages that is the foundation of Medan City. The problems experienced by the community in Tuntungan II Village in the context of political literacy cannot be separated from several factors that cause stagnation of community knowledge about politics and democracy, resulting in 2019 political participation in Tuntungan II Village becoming one of the lowest percentages of political participation in Pancur District. Batu, this is due to a lack of knowledge in choosing leaders or people's representatives in democratic parties, limited networks to understand the importance of elections, and it cannot be denied that the low quality of government administration cannot be separated from the role of community political participation in Tuntungan II Village. This dedication to political education is one of the efforts that will be carried out to increase public knowledge about the importance of politics, the intelligence of voters in choosing which will lead to improving the quality of democracy in North Sumatra. The method that will be used to achieve this goal is community education through interactive discussions, training for the community which will be carried out on an ongoing basis in all villages/sub-districts throughout Deli Serdang Regency which will be implemented in stages and continuously.